Адам Гуровський: сенсаційний волинянин у дискурсі американської популярної літератури XIX сторіччя - Калініченко, Михайло; Kalinichenko, Mykhaylo (Східноєвропейський національний університет імені Лесі Українки, 2014)
Запропоновано принципово нову інтерпретацію творчої еволюції вихідця з Волині, популярного північно-американського автора Адама Гуровського. Акцентовано на потребі ретельного студіювання повноти і складності його зв’язків із дискурсивними радикально-демократичними практиками популярної, сенсаційної літератури.The article introduces a fundamentally novel interpretation of the creative evolution of Adam Guriwski − a native of the Volyn region and a popular North-American author. Sensational publica¬tions, created during his stay in the United States in 1850–1860s, reflected the most essential feature of his personal and creative biography − his ability to easily assimilate, adapt and transform the worldview and aesthetic concepts of American democratic culture. Meanwhile, modern literary historians are confident that the evolution of artistic and political views of Gurowski was influenced primarily by the socio-philosophical thought of the Old World. Such a view completely disregards the American roots of the creative work of Gurowski and leaves totally unnoticed the process of integration of important cultural components of radical democratic discourse in his popular sensational texts. The article accentuates the necessity of careful reexamination of the totality and complexity of his connections with the discursive practice of radical-democratic popular sensational literature of the XIX century.
Adam Gurowski: a Sensational Native of Volyn in the Discourse of American Popular Literature of the XIX Century
Калініченко М. Адам Гуровський: сенсаційний волинянин у дискурсі американської популярної літератури XIX сторіччя Михайло Калініченко // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 34-39.
Keywords: історія північноамериканської літератури; Волинь; Адам Гуровський; дискурс; радикально-демократична; сенсаційна література; history of North-American literature; Volyn; Adam Gurowski; discourse; radical-democrats; sensational literature